KANDUNGAN FOSFOR DAN KADMIUM PADA TANAH DAN BERAS SERTA RISIKO KADMIUM BAGI KESEHATAN PENDUDUK DI KELURAHAN TARUS - Yovita Yasintha Bolly (Agriculture Faculty of Flores University, 2012)
This research was conducted in Tarus Village, Kupang regency, in May until June 2013, to find out the amount of phosphorus and cadmium content in the soil of rice, and to compare the Cd with a threshold concentration of Standard National Indonesia 7387:2009, as well as to predict the magnitude of the risk to the health. This research is descriptive experimental design with 12 samples of soil and rice. Levels of soil–available P is analyzed using the methods of Olsen, whereas, the levels of Cd from the soil and rice are analyzed in the laboratory with the method of analysis of heavy metals in soils and plants, set by Hall of geochemical soil, the Ministry of agriculture. The results of the analysis of land-available Pranging from low – high, but it is not the only deciding factor the amount of Cd in soil and rice. Laboratory analysis results towards rice Cd, shows there are six samples that undetectable levels of Cd, six other samples detected and then described the risk once compared with the standard quality raw and analysis of health risks. The results of the analysis of the levels of Cd shows all rice samples were still below standard quality raw i.e. 0,4 mg kg-1. Risk analysis indicates that there are two samples of rice produced from the paddy fields are not safe for consumption for the duration of 30 years. While the four other samples were a risk for the duration of the 60 years.